Silencing Mediator of Retinoid and Thyroid Hormone Receptors (SMRT) regulates glucocorticoid action in adipocytes. (15th May 2015) - Emont, Margo P.; Mantis, Stelios; Kahn, Jonathan H.; Landeche, Michael; Han, Xuan; Sargis, Robert M.; Cohen, Ronald N.
Highlights: SMRT is a corepressor for nuclear receptors. SMRT represses ligand-dependent glucocorticoid receptor (GR) activation. SMRT regulates glucocorticoid effects on adipocyte function. These experiments highlight a novel role for SMRT in metabolism. Design of selective GR ligands must take into account the role of SMRT in GR action. Abstract: Local modulation of glucocorticoid action in adipocytes regulates adiposity and systemic insulin sensitivity. However, the specific cofactors that mediate glucocorticoid receptor (GR) action in adipocytes remain unclear. Here we show that the silencing mediator of retinoid and thyroid hormone receptors (SMRT) is recruited to GR in adipocytes and regulates ligand-dependent GR function. Decreased SMRT expression in adipocytes in vivo increases expression of glucocorticoid-responsive genes. Moreover, adipocytes with decreased SMRT expression exhibit altered glucocorticoid regulation of lipolysis. We conclude that SMRT regulates the metabolic functions of GR in adipocytes in vivo . Modulation of GR–SMRT interactions in adipocytes represents a novel approach to control the local degree of glucocorticoid action and thus influence adipocyte metabolic function.